Geochemistry and metamorphism of the Mouriscas Complex, Ossa-Morena/Central Iberian zone boundary, Iberian Massif, Central Portugal: Implications for the Cadomian and Variscan orogenies - Henriques, S.B.A. (2020)
ABSTRACT: The Mouriscas Complex is a deformed and metamorphosed predominantly mafic igneous complex of Ediacaran and Ordovician age and crops out at the Ossa-Morena/Central Iberian zone boundary in the Iberian Massif, Central Portugal. It comprises amphibolite with Neoproterozoic protoliths (ca. 544 Ma), protomylonitic felsic dykes derived from younger trondhjemitic protoliths (ca. 483 Ma) and garnet amphibolite derived of even younger dioritic protoliths (ca. 477 Ma). The protoliths of the Neoproterozoic amphibolites are calc-alkaline magmas of basic to intermediate compositions with intraplate and active continental margin affinities and are considered to represent the final phase of the Cadomian arc magmatism. They are interpreted to have originated as coarse-grained intrusions, likely gabbro or diorite and generated from the, partial melting of meta-igneous lower crust and mantle. Their emplacement occurred near the Cadomian metamorphic event dated at ca. 540 Ma (P = 7-8 kbar and T = 640-660 degrees C) which is interpreted to represent a continental collision. During the Late Cambrian-Early Ordovician an extensional episode occurred in the central-southern Iberian Massif and was also observed in other areas of the Variscan Orogen. It led to mantle upwelling and to the development of an aborted intracratonic rift located at the Ossa-Morena/Central Iberian zone boundary and to the opening of the Rheic Ocean to the south of the area studied in present coordinates (i.e., between the Ossa-Morena and South Portuguese Zones). This event has been dated at ca. 477 Ma and was responsible for the melting of deep ancient mafic crust and mantle with formation of bimodal magmatism in an intra-plate setting, as indicated by the protoliths of the protomylonitic felsic dykes with trondhjemitic composition and of the garnet amphibolite. Subsequent Variscan metamorphism took place under amphibolite facies conditions (P = 4-5.5 kbar; T = 600-625 degrees C) at lower P-T conditions than the Cadomian metamorphic event. It was followed by greenschist retrogression as suggested by the appearance of actinolite rims and formation of chlorite and epidote.